Is high platelet distribution width in the first hours of life can predict hemodynamically significant patent ductus arteriosus in preterm newborns? - Demirel, Gamze; Yılmaz, Aslan; Vatansever, Binay; Taştekin, Ayhan (Taylor and Francis Ltd, 2020)
Aim: To determine whether there is any association between platelet indices within the first hours of life and hemodynamically significant patent ductus arteriosus (hsPDA) in preterm newborns. Patient and methods: A total of 100 preterm infants, gestational age <32 weeks and birth weight <1500 g were analyzed in the study. Complete blood counts obtained within the first 6 hours of life were evaluated for platelet parameters and compared for patent ductus arteriosus (PDA) status. Results: We included 50 infants with hsPDA and 50 controls. Mean gestational week of patients were 28.8 ± 2.4 weeks and mean birth weight of the patients were 1237.5 ± 406 g. Platelet distribution width (PDW) is higher in PDA group compared with the control group (p =.023). The cutoff value of PDW is 11.45 fL for hsPDA with 65% sensitivity and 66% specificity. The other blood parameters including platelet count, platelet mass, and mean platelet volume (MPV) were no statistically different between the two groups. Also, there was no association with the platelet count and the response to the medical therapy. Conclusions: There is no association between hsPDA and the platelet count, platelet mass or MPV in the first day of life. We determined that hsPDA patency was significantly associated with a higher first day PDW level, which is a more specific indicator of platelet activation than other platelet parameters.
Keywords: Patent Ductus Arteriosus; Platelet; Platelet Distribution Width; Preterm